An Analysis of Historical Practice Skills of SMA Laboratorium UM Students in Implementing Mini Projects Module - Faiza Rahmalia; Aditya Nugroho Widiadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
The History subject of the Merdeka Curriculum presents historical practice skills as strands that need to be developed for students. Its position as a new strand, of course, is not free from the risk of problems. This problem occurred in history learning at SMA Laboratorium UM, which has not provided its students with the opportunity to apply historical practice directly. Along with this problem, the UPT Management of the UM Laboratory School developed Mini Projects Module (MPM) teaching materials for social science learning in Grade X. By implementing MPM, students are expected to be able to solve problems from various social science perspectives, such as History, Geography, Economics, and Sociology through field research activities and reporting in the form of photovoice. Therefore, this research aims to analyze the historical practice skills of SMA Laboratorium UM students when implementing MPM. The sample of this research was X6 students who were heterogeneous in nature. This article was written in a descriptive format by applying qualitative research methods to interpret the meaning behind the data from observations, interviews, open questionnaires, and documentation. The results of the research showed that X6 students can practice historical practice skills starting from the stage of collecting sources to compiling historiography through the implementation of MPM. However, these skills have not developed evenly across all students. Therefore, this article is expected to serve as a means of reflection and evaluation in developing historical practice skills.